The integrating role of digital staff maturity in a balanced digital transformation model. - I. M. Stepnov; M. Yu. Telegina (Управленческие науки)
The article is devoted to the theoretical and methodological substantiation of the integrating role of digital maturity of   personnel in the processes of modern transformations of industrial enterprises. The subject of the study was the assessment of the role of company employees within the framework of the proposed balanced digital transformation (DT) model, and its purpose is to establish the relationship between the digital maturity (DM) of employees and methods of its formation, taking into account the priorities of a balanced DT. The methodological basis was the materials of works from the field of organizational institutionalism, applicable to solving the problems of managing digital transformations in industry. The results of the research, carried out using the methods of scientific analysis and synthesis, as well as processing the results of the survey and questionnaires, consist in the formation of new ideas about the model of digital transformation. The article reflects its features such as cyclical nature, the sequence of mandatory stages (formation of corporate digital culture, motivation of staff, practice-oriented mentoring, technology, data analysis and customer influence). As differences from existing approaches, the inclusion of the integrating role of digital maturity of personnel in the digital transformation (DT) processes and consideration of technologies and customer needs only after assessing the readiness of personnel in the formed digital environment is noted. The authors have formed recommendations for the practical implementation of the presented model of balanced digital transformation and the conduct of appropriate survey procedures that may be of interest to specialists in this field.